Method Development for Quantitative Determination of Diosgenin from the Seeds of Fenugreek, Trigonella foenum-graecum L. - A. E. Sukhanov; A. N. Stavrianidi; E. D. Kubasova; A. S. Panasyuk; O. V. Buyuklinskaya (Разработка и регистрация лекарственных средств)
Introduction. Modern pharmacognostic research is aimed at searching for plant biologically active individual compounds (RBAIS) isolated from plant extracts.Aim. Study of the content of the steroid sapogenin diosgenin in fenugreek seeds in plant extracts by HPLC-UV method.Materials and methods. The object of study was raw materials-fenugreek seeds produced as medicinal plant raw materials by LLC «Sage» (Irkutsk). Series of extraction and chromatographic separation by HPLC-UV method were performed.Results and discussion. In this work, the method of diosgenin extraction was successfully optimized (after acid hydrolysis of dioscin with a 5 % aqueous solution of hydrochloric acid when heated for at least 4 hours in a sand bath at a power of 150 W) from raw fenugreek seeds using a 50 % aqueous solution of isopropanol, h.h. A simplified technique for chromatographic separation of diosgenin from fenugreek seed extracts using an isocratic mode of 99.9 % acetonitrile elution (h.h.) was proposed.Conclusion. The average content of diosgenin (after acid hydrolysis of dioscin) in fenugreek seeds, taking into account the humidity of raw materials, is (M ± σ) 5,3 ± 0,05 mg/g (95 % CI: 5,1-5,4 mg/g; n = 6).